Africa’s Migration: Historical and Contemporary Trends, Routes and Destinations in Europe and America, with a Focus on Mexico - Gomes, Cristina (Advances in Social Sciences Research Journal, 2026)
This article discuss the movements of the Black African diaspora around the world, the routes and countries of transit for Black African migrants moving to Europe and the United States. The theoretical and conceptual framework is based on the idea that the colonial history of slavery interweaves with persistent colonial racial legacies and hegemonic whiteness while crossing borders, transit countries, and destination cities: labor exploitation, marginalization, integration policies in urban areas. The case study are Morrocco, Brazil and Mexico as transit countries to reach Portugal and the United States. The methodology is based on a literature review and secondary data analysis of the stocks and flows of regular and irregular South African migrants and refugees, and a comparative method of analysis to contrast racism against Black African migrants in a colonizer (Portugal) and in a colonized country (Mexico). The results show the ways how racism persist through al the journey, crossing borders, countries, facing aggressive environments, even organized crime, and during the integration in the countries of transit and destination.